Characteristics of Patients with Hereditary Angioedema Who Reduced Lanadelumab Treatment Administration Frequency: A Retrospective Observational Study of US Claims Data - Nicole Princic; Kristin A. Evans; Chintal H. Shah; Krystal Sing; Salomé Juethner; Bob G. Schultz (Drugs - Real World Outcomes)
Abstract Background Lanadelumab is the only long-term prophylaxis indicated for reduced administration frequency in patients with hereditary angioedema who have been well controlled for > 6 months. Understanding the characteristics of patients who reduce administration frequency will help identify populations where frequency modifications may be appropriate. Objective We aimed to describe characteristics of patients who did and did not reduce lanadelumab administration frequency to inform real-world dosing regimens, and characteristics indicative of sustained frequency reduction. Methods A retrospective observational study using healthcare insurance data in the USA from the Merative™ MarketScan® Commercial and Medicare Databases identified patients persistent on lanadelumab for ≥ 18 months. Reduced administration frequency was defined as a ≥ 25% decrease in lanadelumab costs during months 7–12 or 13–18 versus 0–6. Hereditary angioedema attack triggers/symptoms and hereditary angioedema-related healthcare encounters, treatment, and costs were assessed. Results Of 54 identified patients, 25 reduced administration frequency. Two patients returned to initial dosing frequency during months 13–18 after reducing during months 7–12. Patients who reduced administration frequency experienced fewer hereditary angioedema attack triggers/symptoms before lanadelumab initiation (baseline) and during months 0–6 than those who did not; they also had a lower mean number of hereditary angioedema-related inpatient admissions, emergency room visits, and outpatient visits during baseline, had fewer claims for acute treatment (60.0% vs 65.5%) and prior long-term prophylaxis (20.0% vs 27.6%), and had lower mean hereditary angioedema treatment costs at baseline ($139,520 vs $233,815) than those who did not. Conclusions This real-world analysis suggests that patients with less frequent hereditary angioedema-related healthcare encounters, lower disease activity, and lower costs within 6 months before lanadelumab initiation are more likely to achieve reduced dosing frequency.